Evidence base of clinical studies on Tai Chi: a bibliometric analysis. - Guo-Yan Yang; Li-Qiong Wang; Jun Ren; Yan Zhang; Meng-Ling Li; Yu-Ting Zhu; Jing Luo; Yan-Jun Cheng; Wen-Yuan Li; Peter M Wayne; Jian-Ping Liu (PLoS ONE, 2015)
BACKGROUND: The safety and health benefits of Tai Chi mind-body exercise has been documented in a large number of clinical studies focused on specific diseases and health conditions. The objective of this systematic review is to more comprehensively summarize the evidence base of clinical studies of Tai Chi for healthcare. METHODS AND FINDINGS: We searched for all types of clinical studies on Tai chi in PubMed, the Cochrane Library and four major Chinese electronic databases from their inception to July 2013. Data were analyzed using SPSS17.0 software. A total of 507 studies published between 1958 and 2013 were identified, including 43 (8.3%) systematic reviews of clinical studies, 255 (50.3%) randomized clinical trials, 90 (17.8%) non-randomized controlled clinical studies, 115 (22.7%) case series and 4 (0.8%) case reports. The top 10 diseases/conditions was hypertension, diabetes, osteoarthritis, osteoporosis or osteopenia, breast cancer, heart failure, chronic obstructive pulmonary disease, coronary heart disease, schizophrenia, and depression. Many healthy participants practiced Tai Chi for the purpose of health promotion or preservation. Yang style Tai Chi was the most popular, and Tai Chi was frequently practiced two to three 1-hour sessions per week for 12 weeks. Tai Chi was used alone in more than half of the studies (58.6%), while in other studies Tai Chi was applied in combination with other therapies including medications, health education and other physical therapies. The majority of studies (94.1%) reported positive effects of Tai Chi, 5.1% studies reported uncertain effects and 0.8% studies reported negative effects. No serious adverse events related to Tai Chi were reported. CONCLUSIONS: The quantity and evidence base of clinical studies on Tai Chi is substantial. However, there is a wide variation in Tai Chi intervention studied and the reporting of Tai Chi intervention needs to be improved. Further well-designed and reported studies are recommended to confirm the effects of Tai Chi for the frequently reported diseases/conditions.